Piezoelectric Biosensor based on ultrasensitive MEMS system - He, Ji-Huan; He, Chun-Hui; Qian, Man-Yu; Alsolami, Abdulrahman Ali (Sensors and actuators. A. Physical., 2024)
The lack of ultrasensitive biosensors is the major challenge in the control of pandemics at the very initial stage, so it is necessary to develop new biosensors for the prompt treatment, and the piezoelectric biosensor based on ultrasensitive MEMS system offers a good opportunity. This paper presents a novel approach using polyvinylidene fluoride (PVDF) unsmooth nanofibers to transfer electronic current. The unique unsmooth surface of these nanofibers provides a high surface energy (geometrical potential), making them highly sensitive to microorganisms (e.g., viruses) absorbed on their surface. The absorption of viruses has an obvious effect on the nanofiber’s displacement and electrical resistivity. This paper presents a mathematical model that demonstrates the system's ultra-sensitivity. This rigorous mathematical analysis shows that even when the pull-in voltage in the PVDF nanofiber changes by just 0.0589 %, a dramatic shift from normal periodic motion to pull-in motion is predicted. This paper provides a new and reliable theoretical way to detect pandemics at the very beginning stage. [Display omitted] •A Polyvinylidene Fluoride(PVDF) nanofiber is used in a micro-electromechanical system.•PVDF nanofiber has good piezoelectric property.•A mathematical model is established to show the extremely sensitiveness of the MEMS-based biosensor.